HUBUNGAN DUKUNGAN KELUARGA DAN PENGAMBILAN KEPUTUSAN KARIER MAHASISWA FAKULTAS ILMU PENDIDIKAN UNNES - Sa'diyah, Halimatus; Hariyadi, Sigit (Universitas PGRI Semarang, 2022)
Students in their career decision making are influenced by many factors that can support the sustainability of their career in the future. One of the factors that can support comes from the ectsternal factor is family support. This research aims to find out the relationship between family support for career decision-making in students of Fakultas Ilmu Pendidikan UNNES. Sampling technique with proportional stratified random sampling method with a sample number of 320 students. Data retrieval is done using a career decision-making scale, and a family support scale. Data analysis techniques use multiple regression techniques with the help of SPSS. The results showed a link between family support and career decision-making (t = 4,178, Î² = 0.249) which indicated the higher the level of student family relationships, the higher the level of career decision-making.The conclusion of this study is there is a positve relationship between family support and career decision making of students in Fakultas Ilmu Pendidikan UNNES.